Biofuls reform in the European Union: Why new ILUC rules will reinforce the WTO inconsistency of EU biofuels policy - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2013)
This paper takes stock of the proposals by the European Commission and members of the European Parliament to amend the Renewable Energy Directive (RED) and how the proposed revisions integrate with the obligations of the European Union in the World Trade Organisation (WTO). The European Commission claims that neither RED nor its new proposal violates WTO rules as the sustainability standards and the new reporting requirement apply equally to domestic and foreign biofuels and feedstock. This paper argues that the proposals are not so innocent and that they will err on the wrong side of core WTO rules. In order to understand why the proposals are likely to run into opposition from these rules - and why other countries will argue that their trading rights have been violated - the paper goes through the WTO inconsistency of RED and why so many scholars and lawyers have concluded that RED would not stand the test in a WTO proceeding. Indeed, the European Union has already been subject to WTO complaints. The first case was resolved when the targeted Member States changed its implementation of RED. The second case has recently been filed in Geneva. (...)
Keywords: 330